Effect of n-butanol/diesel blends on performance and emissions of a heavy-duty diesel engine tested under the World Harmonised Steady-State cycle. (15th October 2021) - Tipanluisa, Luis; Fonseca, Natalia; Casanova, Jesús; López, José-María
Highlights: Blends up to 20% v/v of n-butanol with commercial diesel (EN-590) were evaluated. Impact of n-butanol in each mode of the WHSC and on the full test was studied. N-butanol improved engine performance regardless of load or speed conditions. Butanol blends up to 10% showed favourable engine performance and large PM reduction. N-butanol was most beneficial under high load and low speed conditions. Abstract: In recent years, n-butanol produced from waste or lignocellulosic materials has become an attractive and sustainable green energy source for diesel engines because has a clear potential for the partial substitution of fossil-based diesel fuel. This study aims to analyse the effects of different n-butanol/diesel fuel blends on the performance and exhaust emissions of a Euro V heavy-duty diesel engine following the World Harmonised Steady-State Cycle (WHSC), as well as the effect of each mode on the test averaged results. The blends evaluated here were blends of conventional diesel fuel with 5%, 10% and 20% (by volume) n-butanol. Conventional diesel fuel was used as a reference fuel to compare the performance and emission characteristics of the different n-butanol blends. The main findings show that 10% butanol could be considered as a suitable proportion for blending n-butanol/conventional diesel owing to its favourable performance and reduction in particulate emissions, without significant changes in the gaseous emissions of NOX . Mode-by-mode comparative analysis results show improved engine performance with the use of n-butanol in most modes, regardless of speed or load conditions. CO emissions in general increase, despite the incorporation of n-butanol reduces CO emissions under high-load and low-speed conditions. THC emissions increase with n-butanol, being more critical under cold start conditions. The influence of n-butanol on NOX emissions does not have a clear trend, but it is observed that NO2 emissions decrease in all modes with the use of n-butanol blends, mainly in low load modes.